2021
DOI: 10.1021/acs.orglett.1c02856
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching of ortho-Aminated Arylazopyrazoles with Red Light

Abstract: Bidirectional photoswitching of arylazopyrazoles with visible light is enabled by substitution with pyrrolidine and piperidine in the ortho-position of the phenyl ring. The absorption maxima were red-shifted and the molar absorption coefficients in the visible range increased significantly, allowing the use of blue light (λ = 465 nm) for the E → Z isomerization and red light (λ = 600 nm) for the Z → E isomerization. N-Methylation of the pyrazole leads to an excellent thermal stability of the Z isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
1
33
0
2
Order By: Relevance
“…24,30,31 Since the early 2000s, there has been an effort to design an ideal azoarene photoswitch substituted with aryl groups other than phenyl rings. Reports have shown that the λ max can be redshifted into the visible range by replacing phenyl groups with heteroaryl rings (benzodioxanes, 32 diazinines, 31 pyrroles, 33 pyrazoles 34,35 and imidazoles [36][37][38][39] ) and by functionalizing the aryl groups. 32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] These heteroazoarenes have relatively high E → Z photochemical reaction yields, ranging between 46-98%, and Z-isomer half-lives ranging from 1 second up to 46 years.…”
Section: Introductionmentioning
confidence: 99%
“…24,30,31 Since the early 2000s, there has been an effort to design an ideal azoarene photoswitch substituted with aryl groups other than phenyl rings. Reports have shown that the λ max can be redshifted into the visible range by replacing phenyl groups with heteroaryl rings (benzodioxanes, 32 diazinines, 31 pyrroles, 33 pyrazoles 34,35 and imidazoles [36][37][38][39] ) and by functionalizing the aryl groups. 32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] These heteroazoarenes have relatively high E → Z photochemical reaction yields, ranging between 46-98%, and Z-isomer half-lives ranging from 1 second up to 46 years.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Ravoo and his colleagues reported ortho-pyrrolidine-and ortho-piperidine-substituted AAPZs in which the forward isomerization occurred under blue light (465 nm) and the reverse isomerization occurred under red light (600 nm). 8 However, their best switch, the orthopyrrolidine-substituted AAPZ 3, showed moderate isomerization yields in both directions. Photostationary states (PSSs) of trans−cis and cis−trans conversions consisted of 70% cis isomers and 88% trans isomers.…”
mentioning
confidence: 98%
“…Nonetheless, there is a pressing need to identify red-shifted photoswitches, which ideally can be addressed with near-IR light. Very recently, Ravoo and his colleagues reported ortho -pyrrolidine- and ortho -piperidine-substituted AAPZs in which the forward isomerization occurred under blue light (465 nm) and the reverse isomerization occurred under red light (600 nm) . However, their best switch, the ortho -pyrrolidine-substituted AAPZ 3 , showed moderate isomerization yields in both directions.…”
mentioning
confidence: 99%
See 2 more Smart Citations